Creating portable TOSCA archive for iKnow university management system - Kostoska, Magdalena; Gushev, Marjan; CHorbev, Ivan (IEEE, 2014)
Portability of developed solutions is a huge challenge for both the customers and cloud providers. A typical customer would like to realize a flexible software solution which can be easily deployed on a selected infrastructure or transferred on a cloud environment. Finally, the idea of a software environment independent of a specific cloud provider enables preferable conditions for customers. These portability issues are analyzed for a case study of a custom University Management System - iKnow, used by the University Ss. Cyril and Methodius in Macedonia. This paper presents implementation of a Topology and Orchestration Specification for Cloud Applications (TOSCA) specification to enable a software solution to be deployed on a flexible and portable environment. The motivation to consider the implementation of such a platform is initiated due to the rising number of students that use the iKnow system, reaching the peak during the enrollment periods. A possible solution is to consider the possibility of moving the iKnow system (or its part) to a cloud environment and balance the workload using flexible resources. We conducted research to describe the iKnow system using the TOSCA specification and to enable a rather easy deployment and maintenance. This paper presents the challenges and issues regarding the TOSCA specification while implemented on the iKnow system.